Infraestruturas verdes na amenização de impactos da urbanização: controle pluvial com biorretenção e efeito térmico de fachada verde em residência - Fensterseifer, Paula (2020)
The replacement of natural vegetation by solid impervious surfaces and constructions (buildings, roads, pavements), has been causing serious problems related to urban drainage - such as floods, runoff and silting of rivers - and the ongoing increase in urban temperature. Looking for a change in the basic conceptions of city development, green infrastructure methods started to be applied. This study used two different green infrastructure systems for urban areas and assessed their practicability and potential of mitigating impacts from full-scale prototypes over a year-monitoring. In this study, the following were evaluated: i) the capacity of a small bioretention to promote the attenuation of the qualitative and quantitative impact of pluvial runoff of a medium traffic road; and ii) the thermo-energetic influence of a green facade consisting of deciduous vines on the wall of a social interest residence with high incidence of sunlight. To achieve the objectives related to the first experiment, a bioretention cell of 0.6 m³ storage volume was built by the side of an asphalted traffic lane, which received runoff from urban drainage. Its capacity in attenuating both rainwater volume and pollutant loads carried during rainy events was assessed through quantitative monitoring of the volume difference between the water entering and what comes out of the structure and water quality analysis before and after it passed through the bioretention layers. After carrying out quali-quantitative monitoring of the experiment with bioretention, it was found that, although it acts as a sink in the reduction of Total Coliforms found in urban drainage, it also acted as a source of anions (Fluoride, Chloride, Nitrate and Sulphate) and of Total Solids, mainly Total Dissolved Solids, which imply an increase in the Real Color and Turbidity of the drained water. Quantitatively, the bioretention proved to be efficient in retaining rainwater, where it operated with 100% efficiency in 60% of the monitored rainy events. To achieve the objectives of the second experiment, a green facade was built with Wisteria floribunda plant species, shading the west wall of a single family housing. The thermal influence of the green facade on the house was evaluated by continuous monitoring, verifying the thermal difference between the wall behind the green facade and a bare wall beside it. The green facade showed very satisfactory results throughout the monitoring year, reducing the surface temperature of the protected wall by up to 9 °C in the summer. It is observed that the green facade acted in the thermal reduction of the wall throughout the year, even with the loss of leaves in winter. However, during summer and spring, this effect was more significant. In the summer, throughout the day, the thermal amplitude of the protected wall varied by 8.4 °C, while the amplitude of the bare wall exceeds 17 °C. In winter, this amplitude increased to 13 °C on the protected wall and 15 °C on the exposed wall.